Distribusi Pendapatan Petani Padi Organik di Kabupaten Purbalingga Propinsi Jawa Tengah - Anny Hartati (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2020)
The study was to determine the magnitude of the costs and income of farmers and to determine the distribution of farmers' income. The research uses a survey method by taking census samples and data are analyzed by the Gini Index and Gini Ratio analysis. The results showed that organic rice farming benefited farmers because the net income of farmers per hectare per season was Rp 14.645.643 or farmer revenue is Rp 20.095.247,00 and the total cost of farming was Rp 5.449.604 with R/C of 3,687. It means that for each Rp 1.000 will result in Rp 3.687 revenue. The distribution of income of organic rice farmers amounted to 0,4012, meaning that organic rice farming can evenly distribute farmers' income distribution.